DECISION SUPPORT SYSTEM FOR TEACHER PERFORMANCE ASSESSMENT IN 1 AMBARAWA PRIVATE VOCATIONAL SCHOOL USING TOPSIS METHOD - Wibowo, Andi Satrio (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2020)
In every educational institution, sometimes a teacher performance appraisal system is needed, which aims to improve the quality of good teachers. However, at Ambarawa 1 Public Elementary School, the teacher performance evaluation still uses a manual system, namely the DP3 system where the scores are written on paper in a predetermined format. This takes a long time, considering the many elementary school teachers, with many criteria. This problem makes researchers want to conduct research and design a decision support system for teacher performance appraisal at Ambarawa 1 Elementary Schools. The TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method is one method that is often used in determining a decision, researchers use this method. The existence of this decision support system helps the principal in assessing his subordinates, namely the teacher so that the assessment of teacher performance is appropriate